Clinicopathologic and Immunohistochemical Findings from Autopsy of Patient with COVID-19, Japan - Adachi, Takuya; Chong, Ja-Mun; Nakajima, Noriko; Sano, Masahiro; Yamazaki, Jun; Miyamoto, Ippei; Nishioka, Haruka; Akita, Hidetaka; Sato, Yuko; Kataoka, Michiyo; Katano, Harutaka; Tobiume, Minoru; et al. (Emerging infectious diseases, 2020)
An autopsy of a patient in Japan with coronavirus disease indicated pneumonia lung pathology, manifested as diffuse alveolar damage. We detected severe acute respiratory syndrome coronavirus 2 antigen in alveolar epithelial cells and macrophages. Coronavirus disease is essentially a lower respiratory tract disease characterized by direct viral injury of alveolar epithelial cells.